2018
DOI: 10.3390/ijms19113512
|View full text |Cite
|
Sign up to set email alerts
|

Genomic and Transcriptomic Analysis of Hypercholesterolemic Rabbits: Progress and Perspectives

Abstract: Rabbits (Oryctolagus cuniculus) are one of the most widely used animal models for the study of human lipid metabolism and atherosclerosis because they are more sensitive to a cholesterol diet than other experimental animals such as rodents. Currently, two hypercholesterolemic rabbit models are frequently used for atherosclerosis studies. One is a cholesterol-fed wild-type rabbit and the other is the Watanabe heritable hyperlipidemic (WHHL) rabbit, which is genetically deficient in low density lipoprotein (LDL)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 59 publications
0
9
0
Order By: Relevance
“…Thus, there is an urgent need to develop a more personalized medicine, and to enhance patient care through improved diagnostic sensitivity with more effective interventions in ATH prevention and treatment [4]. In this sense, years of research on the genomic basis of ATH have provided the biomedical community with a knowledge of gene‐related ATH risk factors, such as SNPs [5,6], genes and gene variants [7–9], alterations in DNA methylation [10,11], changes in gene expression [12,13], etc. Nevertheless, in the last years a new player has entered the game of disease‐associated genes: the highly heterogeneous group of non‐coding RNAs, which are progressively becoming important factors for atherosclerosis (and other diseases) research either as biomarkers of disease progression or as pathophysiological intermediates, while their operative interactions highlight the remarkable structural and functional complexity of the human genome.…”
Section: Background Atherosclerosis Progression and The Dark Transcrmentioning
confidence: 99%
“…Thus, there is an urgent need to develop a more personalized medicine, and to enhance patient care through improved diagnostic sensitivity with more effective interventions in ATH prevention and treatment [4]. In this sense, years of research on the genomic basis of ATH have provided the biomedical community with a knowledge of gene‐related ATH risk factors, such as SNPs [5,6], genes and gene variants [7–9], alterations in DNA methylation [10,11], changes in gene expression [12,13], etc. Nevertheless, in the last years a new player has entered the game of disease‐associated genes: the highly heterogeneous group of non‐coding RNAs, which are progressively becoming important factors for atherosclerosis (and other diseases) research either as biomarkers of disease progression or as pathophysiological intermediates, while their operative interactions highlight the remarkable structural and functional complexity of the human genome.…”
Section: Background Atherosclerosis Progression and The Dark Transcrmentioning
confidence: 99%
“…e authors reported that NAFLD was consistently associated with coronary artery soft plaque, suggesting early atherosclerosis [5]. ere are many etiological and pathological similarities between atherosclerosis and NAFLD, including hypercholesteremia and hypertriglyceridemia, which lead to lipid deposition in tissue and cause inflammation and fibrosis [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Rabbit genome information is now available from the National Center for Biotechnology Information database at http://www.ncbi.nlm.nih.gov/sra, and a comprehensive database containing both rabbit genome and transcriptome information has been comprehensively constructed by the Chinese Academy of Sciences 73) at http://www.picb.ac.cn/RabGTD/. Fan et al 74) identified 29.8 million single nucleotide polymorphisms and 1.6 million small indels in the 30 genomes in WHHLMI rabbits in the above rabbit genome analyses, suggesting the difficulty in the detection of the gene(s) associated with the progression of coronary lesions and the development of myocardial infarction in WHHLMI rabbits.…”
Section: Genome Analyses Of Whhlmi Rabbits and Identification Of Serumentioning
confidence: 99%